GuiErBai: a potent inhibitor, exhibiting broadly antitumor effect against cervical cancer in vitro and in vivo - Qin, Hong-en; Peng, Lei; Xu, Yuan-cui; Zhang, Zi-xiong; Tian, Ren-fu; Wan, Zhong-xian; Pu, Dao-jing; Li, Hong-chun; Wu, Fei; Zheng, Liangdong; Xu, Xian-shun (Frontiers in Pharmacology, 2024)
Introduction: Cervical cancer (CC) ranks as the fourth most prevalent malignant tumor among women worldwide, and is the fourth leading cause of cancer-related mortality. GuiErBai (GEB), a compound preparation developed by our research team, is derived from the ancient Chinese medicine of the Miao nationality and is comprised of podophyllotoxin (PTOX), imperatorin, isoimperatorin, and A. dahurica alkaloids. These individual components have demonstrated notable efficacy in tumor treatment. However, the specific anti-tumor effect of the compound Chinese medicine GEB in the context of CC has yet to be validated. Methods: HeLa and SiHa cell lines were utilized for in vitro experiments and treated with 5 mg/mL and 10 mg/mL GEB concentrations, respectively. The cell cycle changes after GEB treatment were assessed using flow cytometry. Transmission electron microscopy was employed to observe autophagic bodies and apoptotic bodies, while MDC staining evaluated the occurrence of autophagy. CCK-8 was used to observe the effect of GEB on cell proliferation, and Transwell assays assessed cell migration and invasion. Western blotting detected cell cycle and apoptosis-related protein expression, along with the expression level of autophagy-related protein LC3I/II. Changes in ROS and mitochondrial membrane potential in cervical cancer cells following GEB treatment were determined using ROS detection and mitochondrial membrane potential detection kits. For the in vivo experiment, a nude mouse model of cervical cancer transplantation based on HeLa cells was established. Experimental animals were divided into negative control, positive control, high-dose GEB (10 mg/mL), and low-dose GEB (5 mg/mL) groups. Results: In HeLa and SiHa cell lines, the G0/G1 phase of tumor cells significantly decreased (p < 0.001), while the G2/M phase increased notably (p < 0.001) following various GEB treatments. Electron microscopy showed GEB promoted apoptotic body and autophagosome formation in both cell lines. Compared to untreated HeLa and SiHa cells, GEB-treated cells exhibited significantly reduced caspase3 protein expression, and substantially increased autophagy-related protein LC3I/II expression. GEB treatment significantly reduced migration and invasion capabilities in both cell lines (p < 0.001), while ROS content and mitochondrial membrane potential were significantly elevated (p < 0.001). GEB effectively inhibited cervical cancer cell proliferation, with the optimal concentration being 10 mg/mL. A successful nude mouse model of cervical cancer transplantation was established using HeLa cells. Post-GEB treatment, the tumor volume and weight in nude mice significantly decreased (p < 0.001), with diminished expression of CD34, VEGF, and caspase3 proteins in tumor tissues. Discussion: GEB exhibits a robust antitumor effect against cervical cancer, both in vitro and in vivo, in a concentration-dependent manner, by regulating autophagy and apoptosis of tumor cells.